2020
DOI: 10.1039/c9cp06082k
|View full text |Cite
|
Sign up to set email alerts
|

Experimental observation of nanophase segregation in aqueous salt solutions around the predicted liquid–liquid transition in water

Abstract: Using ultrafast spectroscopy to determine temperature-dependent structuring of water, solvation of ions and the size of phase segregated domains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…This crystallization is a consequence of the nanosegregation of the solution that leads to the formation of small domains of water, a phenomenon that is already visible in the liquid structure near the melting temperature ( 38 ). Nanosegregation of water, and its connection to ice formation, is a more general phenomenon that has also been observed, for instance, in aqueous salt solutions for a range of concentrations ( 39 41 ).…”
Section: Resultsmentioning
confidence: 85%
“…This crystallization is a consequence of the nanosegregation of the solution that leads to the formation of small domains of water, a phenomenon that is already visible in the liquid structure near the melting temperature ( 38 ). Nanosegregation of water, and its connection to ice formation, is a more general phenomenon that has also been observed, for instance, in aqueous salt solutions for a range of concentrations ( 39 41 ).…”
Section: Resultsmentioning
confidence: 85%
“…This crystallization is a consequence of the nano-segregation of the solution that leads to the formation of small domains of water, a phenomenon whose premises can already be found in the liquid structure near the melting temperature 35 . Nano-segregation of water, and its connection to ice formation, is a more general phenomenon that has also been observed for instance in aqueous salt solutions for a range of concentrations [36][37][38] .…”
Section: Water Crystallization Near and Below The Calorimetric Glass ...mentioning
confidence: 71%
“…The high-frequency oscillations can be well-modeled using the Brownian oscillator function, 29 , 39 or the antisymmetrized Gaussian (ASG) function, 40 , 41 where ω o and ω G are the undamped oscillator frequencies, γ is the damping rate, and σ G is related to the full width at half-maximum (fwhm) of the Gaussian line shape by . It was found that the fast-β mode was following a Brownian oscillator throughout, whereas librations fit a Brownian for n -alkanes except propane and an antisymmetrized Gaussian otherwise.…”
Section: Methodsmentioning
confidence: 99%